Q: A plus 3b plus 5a plus 4b?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

No

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

9a + 3b - 11a - 4b = -2a -b

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

6+7a+6b

Related questions

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

No

20a2b2

6a+7b. This cannot be simplified anymore unless you know a or b.

6b+5a-4b+3a= ? Rearrange it as 5a+3a+6b-4b = 8a+2b

1a+3b 2a+4b=3a +7b

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

9a + 3b - 11a - 4b = -2a -b

2a + 4b

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

-6(a-3b-9c)